2017
DOI: 10.1007/s10695-017-0367-y
|View full text |Cite
|
Sign up to set email alerts
|

Cylindrospermopsin effects on cell viability and redox milieu of Neotropical fish Hoplias malabaricus hepatocytes

Abstract: Cylindrospermopsin (CYN) is a cyanotoxin that is cytotoxic to a wide variety of cells, particularly to the hepatocytes. In this study, the toxic effects of purified CYN were investigated in primary cultured hepatocytes of Neotropical fish Hoplias malabaricus. After isolation, attachment, and recovery for 72 h, the cells were exposed for 72 h to 0, 0.1, 1.0, 10, and 100 μg l of CYN. Then, cell viability and a set of oxidative stress biomarker responses were determined. Catalase, superoxide dismutase, glucose-6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 64 publications
2
13
0
Order By: Relevance
“…In human HUVEC cells, on the other hand, they found a concentration-dependent increase (from 0.375 to 1.5 µg/mL CYN) [ 37 ], and in human intestinal cells, the increase was only evident at the highest concentration tested (2.5 µg/mL) [ 36 ]. Other authors who found a significant increase were Fernández et al [ 39 ], in the rat hepatic cell line Clone 9, and Silva et al [ 63 ], in Hoplias malabaricus hepatocytes. In any case, it has been suggested that the GSH reduction does not contribute significantly to CYN acute toxicity in vivo [ 64 ].…”
Section: Toxicity Mechanismsmentioning
confidence: 99%
See 4 more Smart Citations
“…In human HUVEC cells, on the other hand, they found a concentration-dependent increase (from 0.375 to 1.5 µg/mL CYN) [ 37 ], and in human intestinal cells, the increase was only evident at the highest concentration tested (2.5 µg/mL) [ 36 ]. Other authors who found a significant increase were Fernández et al [ 39 ], in the rat hepatic cell line Clone 9, and Silva et al [ 63 ], in Hoplias malabaricus hepatocytes. In any case, it has been suggested that the GSH reduction does not contribute significantly to CYN acute toxicity in vivo [ 64 ].…”
Section: Toxicity Mechanismsmentioning
confidence: 99%
“…Other authors suggest that oxidative stress may be better defined as a disruption of redox signaling and control [ 58 ]. Table 4 [ 9 , 22 , 24 , 26 , 34 , 35 , 36 , 37 , 38 , 39 , 41 , 59 , 60 , 61 , 62 , 63 ] shows the in vitro studies available in the scientific literature dealing with oxidative stress induced by CYN.…”
Section: Toxicity Mechanismsmentioning
confidence: 99%
See 3 more Smart Citations